Para além do silêncio: a sexualidade entrelaçada nas diretrizes educacionais brasileiras - Marely, Alécio Vaneli Gaigher (2024)
This study investigates the tackling of sexual diversity in the Transversal Contemporary Themes (TCTs) of the National Curriculum Parameters (PCNs) and the National Common Curriculum Base (BNCC) in the context of Brazilian education. Using qualitative documentary analysis and discourse analysis, the study examines the meanings, significations and truths involved in the treatment of these themes in the guiding documents. The theoretical framework articulates Foucauldian concepts of biopower, disciplinary power and sexuality devices with Mbembe's notion of necropolitics, aiming to problematize the place given to sexual diversity in national curriculum policies. In addition, the research exposes the historical trajectory of the institutionalization of sex education in Brazil from a genealogical perspective. The role of schools in deconstructing discriminatory views and promoting sexual rights is discussed, along with an analysis of Latin American legislation on the subject. Gaps and misunderstandings are identified in the approaches of the BNCC and PCNs, which continue to sideline these discussions. Against this oversight, the study advocates the centrality of themes of gender representation and diversity for an emancipatory, democratic education aligned with the secular ideals of the Brazilian state. A number of actions are pointed out for this process in the country's educational reality. It is expected that the reflections engendered here will support the necessary improvements in the incorporation of public education policies, in order to foster pedagogical practices capable of combating prejudice and promoting citizenship and respect for diversity in schools.